2016
DOI: 10.1016/j.anres.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of extracts from five edible mushrooms using different extractants

Abstract: a b s t r a c tExtractions were performed of the total phenolic and flavonoid contents and antioxidant properties of five edible mushroom samplesdLentinus edodes, Volvariella volvacea, Pleurotus eous, Pleurotus sajor-caju and Auricularia auriculardusing three different extractants. Among the three different extractants, 50% (volume per volume; v/v) ethanol was the most suitable for antioxidant extraction from the mushroom samples. The 50% (v/v) ethanolic extract of dried L. edodes contained higher total phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 22 publications
6
66
3
6
Order By: Relevance
“…The moderate degree of correlation (R 2 = 0.47) was observed between DPPH• scavenging activity and total phenol content, while there was not noted any correlation between the radical reduction ability and flavonoid amount. Although many previous studies have shown different antioxidative potential of numerous mushroom extracts and its dependance on species, fungal part (fruiting body, mycelium, spores), as well as solvent kind (polar or non-polar) and concentration (Mau et al, 2005a(Mau et al, , 2005bElmastas et al, 2007;Saltarelli et al, 2009;Ramkumar et al, 2010;Sarikurkcu et al, 2015;Boonsong et al, 2016), our results are the first to show the radical neutralization ability of D. tricolor. The capacity was similar to those of Agaricus bisporus, Clitocybe odora and Lactarius deliciosus basidiocarp methanol and ethanol extracts (EC 50 values were 9.61 mg/mL, 6.77 mg/mL and 8.52 mg/mL, respectively) (Khatua et al, 2013).…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…The moderate degree of correlation (R 2 = 0.47) was observed between DPPH• scavenging activity and total phenol content, while there was not noted any correlation between the radical reduction ability and flavonoid amount. Although many previous studies have shown different antioxidative potential of numerous mushroom extracts and its dependance on species, fungal part (fruiting body, mycelium, spores), as well as solvent kind (polar or non-polar) and concentration (Mau et al, 2005a(Mau et al, , 2005bElmastas et al, 2007;Saltarelli et al, 2009;Ramkumar et al, 2010;Sarikurkcu et al, 2015;Boonsong et al, 2016), our results are the first to show the radical neutralization ability of D. tricolor. The capacity was similar to those of Agaricus bisporus, Clitocybe odora and Lactarius deliciosus basidiocarp methanol and ethanol extracts (EC 50 values were 9.61 mg/mL, 6.77 mg/mL and 8.52 mg/mL, respectively) (Khatua et al, 2013).…”
Section: Resultscontrasting
confidence: 58%
“…The capacity was similar to those of Agaricus bisporus, Clitocybe odora and Lactarius deliciosus basidiocarp methanol and ethanol extracts (EC 50 values were 9.61 mg/mL, 6.77 mg/mL and 8.52 mg/mL, respectively) (Khatua et al, 2013). However, it was several-fold higher than methanol extracts of Polyporus sulphureus and Macrolepiota procera basidiocarps (5.36% and 3.26%, respectively) (Sarikurkcu et al, 2015), but significantly lower comparing with 50% ethanol extracts of Auricularia auricula, Lentinus edodes and Daedaleopsis confragosa, which reduced 20%, 65% and 67% of DPPH•, respectively, at considerable lower concentrations (Vidović et al, 2011;Boonsong et al, 2016).…”
Section: Resultsmentioning
confidence: 81%
“…The effect of ultrasonication time, temperature and solvent to solid ratio on DPPH scavenging activity was closely related to the effects on TPC. Boonsong, Klaypradit, and Wilaipun () observed that the DPPH activity in ethanolic extract of Pleurotus sajor‐caju lies between 20% and 48%. The regression equation relating to DPPH radical scavenging activity as response is represented in terms of coded variables below:…”
Section: Resultsmentioning
confidence: 99%
“…Due to the effects of these bioactive compounds, mushrooms are considered to be a good source of natural antioxidants. 16 In the present study, antioxidant potential of both mushroom species were determined. Thus, both TAS and TOS values of H. leucomelaena were found to be higher than that of S. [17][18][19][20] Compared to these studies, the TAS values of H. leucomelaena were higher than those of all the above mentioned mushrooms except O. olearius and the TAS value of S. coronaria was lower when compared to F. pinicola, G. pectinatum, P. eryngii and O. olearius.…”
Section: Results and Discussion Tas Tos And Osi Valuesmentioning
confidence: 94%